STRATEGI PENGELOLAAN KELAS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK PENINGKATKAN PRESTASI BELAJAR SISWA : (Studi Kasus di SMP Berbasis Pesantren Amanatul Ummah Mojokerto) - Bahroin Budiya; Thoriq Al Anshori (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
The Islamic Religious Education (PAI) teacher at the Amanatul Ummah Islamic Boarding School Mojokerto-Based Middle School is the class manager. In practice in the field, PAI teachers face many obstacles in managing the classroom. The Amanatul Ummah Islamic Boarding School-Based Middle School in Mojokerto has tried to carry out classroom management strategies well and maximally. This is proven by several achievements in academic and non-academic fields. The purpose of this study is to describe classroom management strategies in improving student achievement in Amanatul Ummah Islamic Boarding School Mojokerto-Based Junior High School, and to describe the obstacles and solutions to overcome the obstacles faced. This research is a field research The findings in this study are the classroom management strategy in Islamic Religious Education learning in improving student achievement at the Amanatul Ummah Islamic Boarding School Mojokerto-Based Middle School which includes 4 (four) activities, namely structuring the learning environment, teaching methods for teachers (educators), class administration, and setting behavior and giving motivation to students. Barriers faced by teachers in implementing strategies classroom management consists of internal factors and external factors. Internal factors include motivational factors and students' psychological conditions. External factors include time and media allocation constraints. The inhibiting factor, namely the diversity of characteristics of students, teachers / homeroom teachers who have different understandings in classroom management.